Issues in e-learning standards - T., Kanendran; Savarimuthu, Johnny *; Burra, Venkata Durga Kumar * (Sunway University College, 2005)
This paper will discuss the role of e-learning standards for implementing e-learning applications. We briefly define and describe the issues related to e-learning standards to improve performance and availability of elearning content. We also describe the characteristics of standards important for maintaining high quality elearning contents. The various standards are analyzed and the degree of synergy between different standards organizations is identified. We discuss the life cycle for e-learning standards, and the main types of standards to enable the interchange of components in a learning system. The Malaysian experience is presented as a case study.